Geographies of rescue: the role of rural territories in times of crisis - Ferreiro, Maria de Fátima; Mateus, C. (Royal Geographical Society (with IBG) Annual International Conference 2023, 2023)
To identify the main trends on the research of rural territories (‘the rural and the crisis’) To explorator a case study – ‘integral’ cooperative locatet in a rural territory (Portugal) To design paths of future research